Navigating costs: Undergraduate students perceptions of incorporating the APA guidelines into their assignments (Journal of Applied Learning and Teaching, 2025)
The publication manual of the American Psychological Association (APA) is widely used by undergraduate students across the country for academic writing. While instructors provide guidance on how to correctly implement the guidelines within the manual, many students continue to struggle with this task, often making significant errors in their writing. To explore the challenges students face in applying these guidelines, we adopted a motivational approach, examining the issue through the lens of Situated Expectancy-Value Theory (SEVT), with a particular focus on the perception of cost (i.e., why students may be reluctant to complete the task). One hundred and fifty undergraduate students completed our online survey. Through mixed-method analyses, we explored the multidimensional components of cost, as well as its contributions as a predictor of student burnout. Our results are discussed in terms of recommendations for supporting students’ use of APA guidelines, along with limitations and directions for future research.